(untitled) (Research, Society and Development, 2022)
Brazilian agriculture continues to obtain records in agricultural exports, generating foreign exchange and positive balances in the Trade Balance and ensuring with food security due in this pandemic process in which the world is facing. As most NPK inputs are imported and 90% of this import is represented by the acquisition of Potassium Chloride (KCl). Alternate sources with the potential to recover / maintain fertility rates are sought, which are remineralizers or agrominerals. The experiment was carried out in a greenhouse at the Faculty of Agronomy of the Federal University of Goiás (EA / UFG), Goiânia, Goiás. The experiment is represented by two typical soils from the Cerrado of Goiás. The treatments were increasing doses of the KVB-K remineralizer (0, 30, 60, 120 and 240 kg. ha-1 of K2O) in reference to two products: a remineralizer registered with the Ministry of Agriculture, Livestock and Supply, FMX and soluble source of chloride potassium (KCl). The study had the obtainment of variables height, base diameter, number of leaves and trifolios for soybeans (Glycena max) and number of leaves and tillers for rice cultivation (Oryza sativa).